APPLIED LAMINATION FIBERGLASS TO PROTECT AND MAINTENANCE WOOD FISHING VESSEL - Sunardi Sunardi (Journal of Innovation and Applied Technology, 2016)
ABSTRACT               Application of fiberglass lamination is the best way in wooden fishing vessel maintenance and improvement. Fiberglass lamination will improve the hull as waterproof hull, increase strength, smoother surface and more protection against marine fouling. There are several steps of fiberglass laminationfor wooden vessel, the first step is drying and cleaning the wooden vessel from the paint and fouling. The second step is laminating the hull with 2 layers of fiberglass and followed with compound spackling and the last step painting. Based on economical analysis, fiberglass lamination has more advantages compared to conventional repair method. By using fiberglass lamination the nest maintenance activity is only cleaning the moss. From point of performance view, fiberglass lamination will reduce the skin friction resistance and increases the speed and the efficiency of the ship. This speed increase and efficiency are caused by the hull which no more absorb water. Due to no water absorption, the weight of the vessel will be maintained as its dry weight and finally will reduce fuel consumption.  Keywords:  Lamination, Fiberglass, wood, maintenance, efficiency